2001
DOI: 10.1177/0272431601021002002
|View full text |Cite
|
Sign up to set email alerts
|

Possible Selves and Negative Health Behaviors During Early Adolescence

Abstract: The relation of the possible selves to cigarette smoking and alcohol consumption was the focus for this study. Participants (1,606 students in Grades 6 through 9) listed their possible selves and reported their cigarette and alcohol use. The results revealed that adolescent cigarette smoking and alcohol use were related negatively to (a) the number of positive expected selves and (b) the balance between expected selves and feared selves. However, when both possible-selves variables were entered in the model si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
0
29
0
2
Order By: Relevance
“…This finding is similar to previous evidence that positive possible selves may be protective against risk behaviors. For example, Aloise-Young et al (2001) found that the number of positive expected possible selves predicted lower levels of alcohol and tobacco use in sixth- to ninth-graders. Newberry and Duncan (2001) found that high school adolescents with lower levels of delinquent behaviors had more positive possible selves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is similar to previous evidence that positive possible selves may be protective against risk behaviors. For example, Aloise-Young et al (2001) found that the number of positive expected possible selves predicted lower levels of alcohol and tobacco use in sixth- to ninth-graders. Newberry and Duncan (2001) found that high school adolescents with lower levels of delinquent behaviors had more positive possible selves.…”
Section: Discussionmentioning
confidence: 99%
“…Possible selves are cognitive structures that include vivid images of the self in the future state along with procedural knowledge in the form of strategies for either achieving or avoiding possible selves (Cross & Markus, 1991; Markus & Nurius, 1986). They are powerful predictors of adolescents’ behavior (Aloise-Young, Hennigan, & Leong, 2001; Newberry & Duncan, 2001; Oyserman, Bybee, & Terry, 2006; Oyserman & Markus, 1990a, 1990b). As modifiable memory structures, possible selves may be a promising intervention target, particularly in the formative stages of identity development (Oyserman, Terry, & Bybee, 2002), but have yet to be explored in relation to alcohol use in adolescence.…”
Section: Possible Selvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the impact of feared delinquency specifically may be an important step in understanding the link between feared possible selves and delinquent behavior. Most studies examining possible selves have assessed either the motivational impact of positive, expected selves (Aloise-Young et al, 2001) or balance among various possible selves irrespective of a specific domain (i.e., by matching positively valenced and negatively valenced possible selves in the same categories; Oyserman & Markus, 1990a, 1990b; Oyserman & Saltz, 1993). By matching positively valenced possible selves with negatively valenced possible selves in the same domains, researchers obtain a general calculation of factors that individuals both hope for (on the positive end) and fear (on the negative end).…”
Section: Possible Selvesmentioning
confidence: 99%
“…However, a feared delinquent possible self may be a distinctly important construct in its own right. Evidence suggests the merit of investigating types of possible selves separately (i.e., count of feared possible selves) and in specific domains (e.g., delinquency; Oyserman et al, 2004; Aloise-Young et al, 2001). …”
Section: Possible Selvesmentioning
confidence: 99%